INFORMASI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 1 MUARA BUNGO BERBASIS WEB - Nilawati -; Riswan -; M.Roji Fahlevi (JURNAL AKADEMIKA)
In terms of monitoring the activities of the students of SMK Negeri 1 Muara Bungo still not perfect. The system can not be used directly to parents. Parents still difficult to know whether their children actually attend school. The program is also used to facilitate school information to students as well as student trustee. Based on the condition, the writer provide a solution using information medi via the website in the Information System of Education SMK Negeri 1 Muara Bungo